Midwifery Care for Pregnant Women in the First Trimester with Emesis Gravidarum through Red Bean Porridge at PMB Bd. Misni, Pulo Bandring District - Delimayani; Ari Nugraha; Putri Winarsih (Sean Institute, 2025)
One problem that pregnant women need to avoid is weight loss during pregnancy, which can be caused by emesis gravidarum or nausea and vomiting. To increase weight, one way that can be done is by giving red bean porridge. This study aims to determine the effectiveness of giving red bean porridge to pregnant women with nausea and vomiting on weight gain. At PMB Bd. Misni S.Tr, Keb, the number of pregnant women in the first trimester with complaints of nausea and vomiting was 1 person or 10%. This study was conducted once a week on June 15, 22, 29, and July 6, 2025.